The Role of Jackfruit (Artocarpus heterophyllus) Powder in Improves Tenyi Vo Pig Health and Haematological Profile - Choudhary, Jagdish; Nizamuddin; Zuyie, R.; Rutsa, M. Catherine; Savino, N.; Sangtam, Tsarila Z.T.; Sharma, Anju (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Dietary interventions are critical for maintaining health and reducing disease in pig farming, particularly for indigenous breeds like the Tenyi Vo pig in Nagaland, India. This study assessed the effects of jackfruit (Artocarpus heterophyllus) powder supplementation on haematological profile and health outcomes in Tenyi Vo pigs. Twenty weaner piglets (60 days old) were assigned to four groups: G1 (control, concentrate feed), G2 (25 g/kg jackfruit powder), G3 (50 g/kg), and G4 (75 g/kg) for nine weeks. Haematological profile included red blood cells (RBC), white blood cells (WBC), haemoglobin (Hb), packed cell volume (PCV), and mean corpuscular volume (MCV). Morbidity and mortality were monitored. The G4 group showed the highest RBC (6.86 x 106/mm3), WBC (22.95 x103/µL), Hb (13.13 g/dl), PCV (37.15%), and MCV (56.23 fl), with significant differences (P<0.05). No morbidity or mortality occurred in G3 and G4, unlike G1 and G2 (15% morbidity, 5% mortality). Jackfruit powder at 75 g/kg enhances haematological health and reduces disease incidence, supporting its use in pig diets.